Reviews - Philip Barker; Kathy Buckner; Debra Fayter; Peter Dwyer; Steve Green; Bill Hubbard; Lorraine Warren (Association for Learning Technology, 1997)
For a variety of different reasons, increasing use is now being made of the Internet for the delivery of course materials and/or for the support of teaching and learning activities. The details of the mechanisms used will obviously vary from one situation to another, depending upon the types of problem to be addressed. These may involve mentoring, teaching, monitoring, recording, tutoring, assessing, and so on. In this book, the author attempts to review the educational and administrative considerations of offering courses, course materials or course delivery via the Internet.